Identification of de novo variants in KCTD10 as a proposed cause for multiple congenital anomalies - Michelle M. Morrow; Erin Torti; Bobbi McGivern; Ryan Gates; Mir Reza Bekheirnia; Nasim Bekheirnia; Leandra Folk; Shannon Holtrop; Timothy Blake Palculict; Olivia L. Redlich; Adi Reich; Maria J. Guillen Sacoto; et al. (HGG Advances)
Summary: To date, the KCTD10 gene (MIM: 608726) has not been definitively associated with a human disease, although studies in animal models suggest that it plays a role in embryonic development. We have identified multiple unrelated individuals with de novo missense variants and overlapping phenotypes, including congenital heart anomalies and congenital anomalies in other organ systems, in our internal database. This report includes a detailed description of the genotype and phenotype for two consented individuals and aggregate data of additional individuals who were not available for case-specific publication. Based on the data presented here, we propose that damaging de novo missense KCTD10 variants are associated with an autosomal dominant phenotype that includes cardiac and other congenital anomalies. We encourage additional studies to further characterize this condition and identify a mechanism for disease.